Pengaruh Pemberdayaan Masyarakat terhadap Upaya Pengembangan Desa Wisata - Candra Setiawan; Nana Darna; Nurdiana Mulyantini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Sadana District implements community-based tourism as an empowerment approach that involves and places the community as an important actor in the context of a new development paradigm, namely sustainable development (Sustainable Development Paradigm). The purpose of community empowerment itself is basically to improve the knowledge, attitudes, and skills of each individual, so that they have the ability to work and strive independently in order to improve their quality of life. In addition, the purpose of empowerment is to increase the potential of the community in order to be able to improve a better quality of life for all community members through self-help activities (Sutarto, 2007:153) This type of research is field research directly from the community through interviews, documentation and other tools which are primary data. Primary data was obtained by themselves from the community and still needs further analysis. Field research is a research that aims to research something that happens in the community, in this case the location to be studied is in Bendasari Village, Gunungsari Village and Tanjungsari Village, Sadananya District, Ciamis Regency. The nature of the research used in this study is qualitative descriptive research. The definition of descriptive is research that seeks to tell a solution to existing problems based on data, presenting data, analyzing and interpreting. The qualitative research is data collection carried out under natural conditions, primary data sources and data collection techniques are more on in-depth observation and interviews and documentation. Qualitative research is to make a systematic, factual and accurate analysis of facts or characteristics of a certain population or region. Based on the description of the results of the research and discussions that have been carried out, the researcher can draw conclusions, including the development efforts in the Bendasari, Tanjungsari, and Gunungsari Tourism Villages taken through: (a) Human resource development is carried out through training, discussions, and others. (b) Partnership with River Tubing, Taruna Karya, PLN, the Resque sector, and parties engaged in the tourism sector. (c) Village Government activities, namely holding meetings, discussions, and sports together. (d) Promotion through social media, through word of mouth, publication. (e) Festival or competition, namely a songbird competition held at the Bukit Bubulak tourist attraction, Bendasari Village. (f) Fostering community organizations by inviting the community to participate in the management of Tourism Villages. (e) Cooperation with universities or universities in Ciamis Regency and its surroundings.